DETERMINATION OF RADIOISOTOPE CONCENTRATION IN MINING SAMPLES WITH THE SIMPLE AND NEUTRON ACTIVATION ANALYSIS IN WEST TIMOR ISLAND EAST NUSA TENGGARA - Bartholomeus Pasangka; Kirbani Sri Brotopuspito; Herry L. Sianturi (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2019)
Abstract [Determination of Radioisotope Concentration in Mining Samples with The Simple and Neutron Activation Analysis in West Timor Island East Nusa Tenggara] The nature of Timor island have contents of several kinds of mining mineral, which still buried in rock, one of them is radioisotope that deposit activity concentration in the rock is unknown. This radioisotope is needed in several sectors as an alternative energy sources that begin to be developed in Indonesia. Problems specifications were studied in this research about activity concentration of radioisotope in the sample of mining and investigate of its prospect. The methods of research comprise of observe/ survey, sampling, analysis, and interpretation, which are applied in two analysis modes: 1) the simple analysis, and 2) neutron activation analysis (relative method). The steps of sample processing consist of: 1) grouping, 2) drying, 3) refining I, 4) burning, 5) refining II, 6) balancing, 7) stabilizing, and 8) drying again. The last processing results the softes dust. Furthermore procedures with the simple analysis comprise of: 1) to count sample, 2) to correct with background, 3) to calculate concentration of radioisotope element within the mine sample. The procedures for neutron activation analysis: 1) the softest dust sample is put into the polyethilene capsule and irradiated together with standard sample, then refrigerated during one week, 2) to countfield and standard sample on the same time and detector is same calibrated, 3) to correct with background, 4) to calculate concentration of radioisotope element within the mine sample. The results of research: activity concentration of radioisotope deposit in mining samples at sub-district ofAmarasi Kupang Wast Timor Island with simple analysis about 4.36 x 10 µCi/ gram, result with neutron activation analysis about 43.8 part per million or 4.38 x 10-5 µCi/ gram up to 2.34 x 10 -4 unit up to 235.3 part per million or 2.353 x 10 -5 unit. Activity concentration of radioisotope deposit in mining samples give stimation that radioisotope deposit in mining samples is possible prospect for exploration but still necessary another data. Key words: determination; concentration; radioisotope; miningAbstrak Alam pulau Timor menyimpan berbagai jenis mineral tambang yang masih terpendam dalam batuan, salah satu di antaranya adalah radioisotop yang konsentrasi deposit dalam batuan belum diketahui. Rradioisotop tersebut diperlukan dalam beberapa bidang sebagai salah satu sumber energi alternatif yang sudah mulai dikembangkan di Indonesia. Spesifikasi masalah yang dikaji dalam penelitian ini menyangkut konsentrasi aktivitas radioisotop dalamsampel bahan galian dan menyelidiki keprospekannya. Metode penelitian meliputi observasi/survei, sampling, analisis, dan interpretasi, yang diterapkan dalam dua model analisis: 1) analisis sederhana, dan 2) analisis aktivasi neutron (motode nisbi). Langkah-langkah pengolahan sampel terdiri atas: 1) pengelompokan, 2) pengeringan, 3) penghalusan I, 4) pembakaran, 5) penghalusan II, 6) penimbangan, 7) penstabilan, dan 8) pengeringan. Pengolahan akhir menghasilkan debu sangat halus. Prosedur selanjutnya dengan analisis sederhana meliputi: 1) mencacah sampel, 2) mengoreksi dengan cacah latar, 3) menghitung konsentrasi radioisotop dalam sampel bahan galian. Prosedur untuk analisis aktivasi neutron: 1) sampel debu sangat halus dimasukkan ke dalam kapsul polyethilena dan diiradiasi bersamaan dengan sampel standar, kemudian didinginkan selama satu minggu, 2) mencacah sampel lapangan dan sampel standar padawaktu yang sama dengan detektor yang terkalibrasi sama, 3) mengoreksi dengan cacah latar, 4) menghitung konsentrasi radioisotop dalam sampel bahan galian. Hasil yang diperoleh: konsentrasi aktivitas deposit radioisotop dalam sampel bahan galian di Kecamatan Amarasi Kupang pulau Timor barat, berkisar antara 4,36 x 10 μCi/ gram sampai dengan 2,34 x 10 -5 satuan sampai dengan 235,3 ppm = 2,353 x 10 -4 μCi/ gram (analisis sederhana), dan 43,8 ppm = 4,38 x 10 -5 satuan (analisis aktivasi neutron). Konsentrasi aktivitas deposit radioisotop dalam sampel bahan galian memberikan gambaran bahwa deposit unsur dalam bahan galian tersebut kemungkinan prospek untuk eksplorasi (masih perlu data lain). Kata kunci: determinasi, konsentrasi, radioisotop, tambang